COOLING SYSTEM FOR PHOTOVOLTAIC PANELS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This study focuses on the heating of a PV panel subject to infrared irradiance and the electric load-related Joule effect, as reducing the temperature of the PV panel may increase the PV conversion efficiency. A water-circulated heat exchanger is provided on the back of the PV panel to minimize the hotspot temperature. The heat thus extracted out of the system may be further used in a secondary energy conversion system.
Keywords: Photovoltaic panel; Single flow cooling system; Infrared irradiance; Joule effect; Numerical simulation